2013
DOI: 10.1210/jc.2013-2016
|View full text |Cite
|
Sign up to set email alerts
|

Calcitriol-Mediated Hypercalcemia: Causes and Course in 101 Patients

Abstract: Hypercalcemia mediated by calcitriol remains a rare presentation. In almost half the cases, sarcoidosis was the underlying cause, whereas a third of patients had cancer or systemic infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 28 publications
2
53
1
Order By: Relevance
“…Of those reported, only one was a neuroendocrine tumour 5. Nonetheless, an Australian retrospective case series of patients with calcitriol-mediated hypercalcaemia found that 5% of cases were associated with solid tumours 2. This evidence suggests that overproduction of 1,25(OH) 2 D may be an under-reported cause of hypercalcaemia in patients with solid malignancies and a comprehensive work-up should be performed for these patients, especially as this could have implications for management.…”
Section: Discussionmentioning
confidence: 99%
“…Of those reported, only one was a neuroendocrine tumour 5. Nonetheless, an Australian retrospective case series of patients with calcitriol-mediated hypercalcaemia found that 5% of cases were associated with solid tumours 2. This evidence suggests that overproduction of 1,25(OH) 2 D may be an under-reported cause of hypercalcaemia in patients with solid malignancies and a comprehensive work-up should be performed for these patients, especially as this could have implications for management.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective case series found that of 101 patients with hypercalcaemia and elevated or inappropriate normal calcitriol, sarcoidosis was the most common aetiology (49%). Haematological malignancy was second at 17%, with infections at 8% 5. A much less common aetiology of hypercalcaemia is from silicone injections.…”
Section: Discussionmentioning
confidence: 99%
“…By inhibiting 1-alpha-hydroxylase, steroids (hydrocortisone, prednisone) will prevent the conversion of precursor 25-hydroxyvitamin D into calcitriol [8]. Additionally, in such cases of vitamin D-mediated hypercalcemia, restriction of dietary calcium is needed.…”
Section: Long-standing Treatment Strategies For Hcmmentioning
confidence: 99%
“…Excessive calcitriol production by tumor cells leads to an increased absorption of both calcium and phosphorus from the intestinal tract and osteoclastmediated bone resorption [8]. An even more rarely reported cause of HCM is the ectopic production of authentic PTH by tumoral cells [1,9].…”
mentioning
confidence: 99%